Amidation/non‐amidation top‐down analysis of endogenous neuropeptide Y in brain tissue by nano flow liquid chromatography orbitrap Fourier transform mass spectrometry. (23rd March 2021) - Yamagaki, Tohru; Kimura, Yuka; Yamazaki, Takashi
Abstract: Neuropeptide Y (NPY) is a transmitter molecule in nerve system, and it was an over 4‐kDa large peptide with the C‐terminal end amidation. NPY is biosynthesized through many maturation processes from a large pre‐pro‐peptide with peptide‐cleavages and amidation that is important to study the biosynthesis regulation. Previously, it was reported that cathepsin L participates in the production of NPY and that cathepsin L generates both of amidated and non‐amidated NPYs. However, the non‐amidated NPY (NPY‐COOH) has not been reported in brain tissues until now. In this study, endogenous NPY‐COOH in mouse brain tissue was detected and identified by using nano flow liquid chromatography (nanoLC) orbitrap Fourier transform mass spectrometry (FT‐MS) after the effective purification and separation of NPY‐COOH from NPY‐amide and other peptides using two different gel‐filtration chromatography. Amidated NPY was eluted earlier than non‐amidated NPY‐COOH in the C18 reversed phase nanoLC and the silica‐based gel‐filtration chromatogram with hydrophobic interaction. The amount of endogenous NPY‐COOH was about 0.05% of the matured NPY‐amide amount in adult mouse brain.